Optimizing infectious disease diagnostics through AI-driven hybrid decision making structures based on image analysis - Ahsan, Muhammad; Damaševičius, Robertas; Shahzad, Sarmad (Zielona Góra: Uniwersytet Zielonogórski)
Infectious diseases significantly impact global mortality rates, with their complex symptoms complicating the assessment and determination of infection severity. Various countries grapple with different forms of these diseases. This research utilizes three AI-based decision-making techniques to refine diagnostic processes through the analysis of medical imagery. The goal is achieved by developing a mathematical model that identifies potential infectious diseases from medical images, adopting a multi-criteria decision-making approach.
Keywords: medical imaging; fuzzy logic; disease diagnostics; decision support; health informatics